The reliability and validity of the Lane Agility Test for collegiate basketball players - Brown, Ashley E. (My University, 2012)
Agility is the ability to change body direction, or position in space. The game of basketball requires intermittent starts, stops, changes of direction, etc. Several tests have been developed to measure agility. The purpose of this study was to determine the reliability and validity of the Lane Agility Test (LAT) by comparing this test with the TTest (TT) and Pro Agility Test (PRO). 24 Division III collegiate basketball players performed 3 agility tests on 2 different occasions. The best time recorded for LAT, PRO, and TT were compared. The players' coaches were asked to rank (RANK) each subject on his/her agility in a game. Results were compared with rankings ofLAT, TT, and PRO. Reliability of the LAT was assessed using intraclass correlation coefficient and coefficient of variation. To establish validity, rankings ofLAT, TT, PRO, and RANK were compared using Spearman-Rho correlation. Intrasession reliability ofLAT was very strong for Day 1 and Day 2. Intersession reliability of LAT was also very strong. Very strong Spearman-Rho correlations were found between LAT and TT, LAT and PRO. No significant correlations were found between performance on LAT and RANK. Results support the LAT as a valid and reliability measurement of closed agility.
Keywords: Physical fitness.; Physical education and training.; Basketball - training.